Investor heterogeneity and large-scale asset purchases - Johannes Breckenfelder; Veronica De Falco (European Central Bank (ECB), 2024)
Large-Scale Asset Purchases can impact the price of securities directly, when securities are targeted by the central bank, or indirectly through portfolio re-balancing of private investors. We quantify both the direct and the portfolio re-balancing impact, emphasizing the role of investor heterogeneity. We use proprietary security-level data on asset holdings of different investors. We measure the direct impact on security level, finding that it is smaller for securities predominantly held by more price-elastic investors, funds and banks. Comparing a security at the 90th percentile of the investor elasticity distribution to a security at the 10th percentile, the price impact is only two-thirds as large. To assess the portfolio re-balancing effects, we construct a novel shift-share instrument to measure investors' quasi-exogenous exposure to central bank purchases, based on investors' holdings of eligible securities before the QE program was announced. We show that funds and banks sell eligible securities to the central bank and re-balance their portfolios towards ineligible securities, with investors ex-ante more exposed to central bank purchases re-balancing more. Using detailed holdings data of mutual funds, we estimate that for each euro sold to the central bank, the average fund allocates 88 cents to ineligible assets and 12 cents to other eligible assets that the central bank does not buy in that time period. The price of ineligible securities held by more exposed funds increases compared to those held by less exposed funds, underscoring the portfolio re-balancing channel at work.
Keywords: E52; E58; G11; G12; G23; 330; financial intermediaries; mutual funds; central bank; asset pricing